The Clinical Utility of the Adolescent and Young Adult Psycho-Oncology Screening Tool (AYA-POST): Perspectives of AYA Cancer Patients and Healthcare Professionals - Patterson, Pandora; McDonald, Fiona E. J.; Allison, Kimberley R.; Bibby, Helen; Osborn, Michael; Matthews, Karen; Sansom-Daly, Ursula M.; Thompson, Kate; Plaster, Meg; Anazodo, Antoinette (Frontiers in Psychology, 2022)
Objective: Routine psychosocial screening and assessment of people diagnosed with cancer is crucial to the timely detection of distress and provision of tailored supportive care; however, appropriate screening tools have been lacking for adolescents and young adults (AYAs), who have unique needs and experiences. One exception is the recently validated AYA Psycho-Oncology Screening Tool (AYA-POST) for use with young people aged 15 to 29 years, which comprises a distress thermometer and age-specific needs assessment. This study investigates the clinical utility of this measure, as well as the subsequent service responsiveness within the Australian Youth Cancer Services. Method: In total, 118 AYAs and 29 healthcare professionals completed surveys about the clinical utility of the AYA-POST; a subset of 30 AYAs completed a three-month follow-up survey assessing service responsiveness. Descriptive statistics (frequencies/means) were computed for all items, with chi-square analyses used to explore whether perceived clinical utility varied with AYA age, AYA sex, HCP discipline, or HCP length of time using the AYA-POST. Results: Participants’ responses demonstrate high levels of satisfaction with the tool, evidencing its appropriateness, practicability and acceptability. Moreover, the AYA-POST was reported to facilitate communication about psychosocial needs and prompt referrals, indicating good service responsiveness. Ratings of clinical utility did not differ significantly between AYA or HCP groups. Conclusions: This study demonstrates that the AYA-POST is an appropriate tool in the psychosocial screening of AYAs with cancer, facilitating the identification of distress and unique concerns in this population and valuable in triaging and tailoring care for young cancer patients.